Information systems what every business student needs to know - Mallach, Efrem 1942- (Chapman & Hall/CRC textbooks in computing, 2016)
Most information systems textbooks overwhelm business students with overly technical information they may not need in their careers. Information Systems: What Every Business Student Needs to Know takes a new approach to the required information systems course for business majors